Synchronization of oestrus in Hamdani ewes: The use of different PMSG doses - Timurkan, H; Yildiz, H (Natl Veterinary Research Inst, 2005)
The experiment was performed on 130 Hamdani ewes and 12 Dorset rams were used. The ewes were randomly divided into 4 groups. Intra-vaginal sponges, containing 40 mg of FGA, were left in the vagina of groups 1, 2, and 3 for 14 d. Immediately after removal of the sponges, PMSG hormones at the doses of 500 IU in group 1, 600 IU in group 2, and 750 IU in group 3 were administered intramuscularly. The group 4 served as control. Animals in groups 1, 2, and 3 were inseminated with 0.25 cm(3) of fresh semen 72 and 96 h after PMSG administrations. Ewes in the control group were artificially inseminated during their spontaneous oestrous period. The percentages of ewes showing oestrus in the first 3 groups and control were determined as 100% and 97.05%, respectively. The conception rates in groups 1, 2, 3, and 4 were found as 90.62%, 93.75%, 100% and 79.4%, respectively. The conception rate was higher in groups 2 and 3 than in control and in group 3 than in groups I and 2 (P<0.05). The mean litter size in groups 1, 2, 3 and 4 were 1.06 +/- 0.09, 1.25 +/- 0.11, 1.40 +/- 0.12 and 0.88 +/- 0.09, respectively. The mean litter size in groups 2 and 3 was higher (P<0.05) than in group 4. The gestation period in groups 1, 2, 3, and 4 was 152 +/- 1.89,151 +/- 1.33, 149 +/- 0.95, and 160 +/- 2.95 days, respectively. A significant difference (P<0.05) between 4 groups with regard to the gestation period was found. It was concluded that FGA and PMSG administration in the Hamdani ewes in the breeding season may be useful to condense oestrus and parturition and in order to increase pregnancy rate.
Keywords: Hamdani ewe; progestogens; PMSG; reproductive performance